Pengaruh Earning Per Share (EPS), Rasio Profitabilitas Dan Price Earning Ratio (PER) Terhadap Harga Saham (Pada Study Empiris Perusahaan Real Estate And Property Di Bursa Efek Indonesia Tahun 2011-2013) - Aditya, Dodi Indra; , Drs. Wiyadi. MM, P.HD (2016)
This study aimed to analyze the influence Earning Per Share (EPS), Profitability Ratios Price Earning Ratio (PER) to the stock price on the real estate and property companies listed on the Stock Exchange period 2011-2013. This research was conducted using secondary data. The population in this study throughout the company's Real Estate and Property listed on the Indonesia Stock Exchange (IDX) with a sample of 51 observations with purposive sampling technique. Before testing the hypothesis first performed classical assumption that include normality test, multicollinearity, autocorrelation and heteroscedasticity test. The results of this study prove that partially Earning Per Share (EPS), Profitability Ratios significant effect on the stock price on the real estate and property companies listed on the Stock Exchange period 2011-2013. While Price Earning Ratio (PER) no significant effect on the price of shares in real estate and property companies listed on the Stock Exchange period 2011-2013. The research model used in this study is right or fit.